2014
DOI: 10.1007/s12648-014-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Melnikov analysis and chaos control of nonlinear dispersive KdV equation under external periodic perturbation

Abstract: The behavior of non-smooth solitary waves switching to chaos is studied. Firstly, we present some singular homoclinic orbits of an unperturbed system. These singular homoclinic orbits correspond to non-smooth solutions. Secondly, we find that the peculiar solitary waves are more likely to be chaos by using the Melnikov theory. Finally, chaos thresholds under different amplitudes and frequencies of a periodic perturbation are given. One interesting finding is that there exists a peculiar perturbation frequency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this context, Cajori and Farlow obtained the first exact solution to the linear wave equation [6,7]. Further researches have been conducted to investigate the nonlinear wave equations where different approximate and numeric methods have been developed; see, for example, [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Cajori and Farlow obtained the first exact solution to the linear wave equation [6,7]. Further researches have been conducted to investigate the nonlinear wave equations where different approximate and numeric methods have been developed; see, for example, [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [20] studied stochastic chaos and its control by the top Lyapunov exponent. Yin et al [21] proved the peculiar solitary waves are more likely to be chaos by using the Melnikov theory and found that the system can be well controlled when the frequency of the perturbation surpasses the peculiar perturbation frequency with fixed parameters of the unperturbed system. Noise, as random phase, has been used in studying the control of chaos in the paper.…”
Section: Introductionmentioning
confidence: 99%